Some extremal problems in the theory of nonoverlapping domains with free poles on rays - Bakhtin, A. K.; Targonskii, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We obtain new results on the maximization of the product of powers of the interior radii of pairwise disjoint domains with respect to certain systems of points in the extended complex plane.